Basalt Rock Dust Amendment on Soil Health Properties and Inorganic Nutrients—Laboratory and Field Study at Two Organic Farm Soils in New England, USA - Justin B. Richardson (Agriculture)
Basalt rock dust (RD) is a rock quarry byproduct that may improve soil health in organic farming systems. RD was applied at two contrasting organic farms (the no-till VT-Farm in Thetford, Vermont, and the tilled MA-Farm in Barre, Massachusetts) and in soil batch reactors to investigate the impacts of basalt RD applications (6.7 tons ha−1) on physical and chemical soil health properties. Triplicate soil pits at two fields (RD and no RD) at each farm were sampled down between 80 to 110 cm depths in 2020. Median coarse (>2 mm) and very coarse aggregates (>50 mm) increased by 15% to 25%, and soil organic carbon concentrations increased by 69% to 135% for RD added, compared to no RD, in the top 20 cm of the soil profile at both farms. Plant-available Ca, Mg, and K increased between 62% and 252% in the top 30 cm for both farms. Plant-available micronutrients (B, Mn, Cu, and Zn) showed limited increases from the RD addition at the two farms. The laboratory batch reactor results confirm the increased Ca and Mg release rates tested across soils, but K, P, and the micronutrient batch reactor results did not increase from the RD addition. One contrary finding was (−41% at the VT-Farm) the lower plant-available P and soluble P (−5 to −29%) under the RD addition, suggesting that further studies on the interactions with Fe and pH from the RD addition are warranted.